Experimental Analysis of the Stratification Characteristics of a Water Storage Tank with New Stratifier - Wang Chongyuan; Zhang Hua; Wang Zilong (Zhileng xuebao, 2016)
Test rig is established to measure the stratification characteristics of a water storage tank with new stratifier. When the initial temperature of the tank is 50℃ and the inlet temperature of the water is 20 ℃, the temperature of each layer in the tank is measured when the flow rate is 1.18 L/min,3.19 L/min,5.20 L/min respectively,. The results show that, when the larger the flow rate is, the larger is the slope of the sudden change in temperature curves, the destruction of stratification is more obvious. Based on the first law of thermodynamics and the second law of thermodynamics, the methods of volume, energy and exergy are used to describe the stratification characteristics of the tank. The results show that, when the flow rate is1.18 L/min,3.19 L/min,5.20 L/min respectively, the extraction efficiency is 93.7%, 95.7%, 96.7% respectively; the discharge efficiency is 98.2%, 95.7%, 92.3% respectively, which indicate that high extraction efficiency and discharge efficiency is got in three flow rates; when the dimensionless time is 0.7, the exergy efficiency is 13.3%, 14.6%, 17.6% respectively, and the stratification is worse for high flow rate than that with low flow rate.